Kontribusi Koordinasi Mata Dan Kaki Terhadap Keterampilan Passing Bermain Futsal Ekstrakurikuler Di SMA Negeri 02 Seluma - Pratama, Oki; Mesterjon, Mesterjon; Syaputra, Roni (Educative Sportive, 2024)
This study aims to determine the Contribution of Eye and Foot Coordination to Passing Skills Playing Futsal at SMA Negeri 02 Seluma with a type of correlation research using test and measurement methods and documentation. The population in this study were extracurricular futsal players at SMA Negeri 02 with sampling using total sampling techniques totalling 21 players. The results of research on the Contribution of Eye and Foot Coordination to Passing Skills Playing Futsal at SMA Negeri 02 Seluma, it can be concluded that there is a significant contribution between the eye and foot with passing skills in extracurricular players at SMA Negeri 02 Seluma with a correlation coefficient of 0.44. With a sufficient category in the ankle coordination variable, namely with an average of 28.5, while the passing skills variable is in the good category, namely with an average of 28 with normal distribution on each variable, namely the ankle coordination variable obtained the result X² is 1.8 ≤ from x² table 32, 671 and in the passing skills variable obtained the result x²count 1 ≤ x²table 32, 671.